The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.annemergmed.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Management, and Transition of Care for Patients With Opioid Use Disorder in the Emergency Department

Abstract: Because of a soaring number of opioid-related deaths during the past decade, opioid use disorder has become a prominent issue in both the scientific literature and lay press. Although most of the focus within the emergency medicine community has been on opioid prescribing-specifically, on reducing the incidence of opioid prescribing and examining alternative pain treatment-interest is heightening in identifying and managing patients with opioid use disorder in an effective and evidence-based manner. In this cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 49 publications
3
77
0
Order By: Relevance
“…5,6 Thus, the ED provides a unique opportunity to initiate appropriate treatment for OUD. [7][8][9] Opioid agonist medications, such as buprenorphine/naloxone (BUP) and methadone, are the current standard of treatment for OUD and have been shown to reduce withdrawal symptoms, craving, relapse, overdose, and mortality (all cause and opioid related). [10][11][12] A 2015 randomized clinical trial involving 329 ED patients with OUD demonstrated that BUP can be safely initiated in the ED and demonstrated that patients receiving BUP in the ED were twice as likely to remain engaged in formal addiction treatment at 1 month (78% vs. 37%, p < 0.001).…”
mentioning
confidence: 99%
“…5,6 Thus, the ED provides a unique opportunity to initiate appropriate treatment for OUD. [7][8][9] Opioid agonist medications, such as buprenorphine/naloxone (BUP) and methadone, are the current standard of treatment for OUD and have been shown to reduce withdrawal symptoms, craving, relapse, overdose, and mortality (all cause and opioid related). [10][11][12] A 2015 randomized clinical trial involving 329 ED patients with OUD demonstrated that BUP can be safely initiated in the ED and demonstrated that patients receiving BUP in the ED were twice as likely to remain engaged in formal addiction treatment at 1 month (78% vs. 37%, p < 0.001).…”
mentioning
confidence: 99%
“…The ED is on the front lines of the opioid overdose epidemic and, as part of the medical safety net and key access point to the health care system, has an essential role in preventing opioid overdose death and facilitating referral to addiction treatment . We found our ED naloxone distribution and community recovery coach consultation program to be overall acceptable to ED providers, had adequate reach and adoption, and was utilized consistently over time without overall significant depreciation 1 year from implementation.…”
Section: Discussionmentioning
confidence: 91%
“…Following an overdose, individuals are at higher risk of death, but some studies have also shown increased enrollment in OUD treatment . Each overdose event and related ED visit, therefore, presents a critical opportunity to prevent not only future overdose death, but also engagement in treatment …”
mentioning
confidence: 99%
“…9 Under the Drug Enforcement Administration's "72-hour rule," buprenorphine can also be administered by nonbuprenorphine physicians for up to 3 days while patients await medication-assisted treatment. 10 Overdose deaths with buprenorphine are less common than with heroin and are most often observed with coingested benzodiazepines. 11 Buprenorphine's ability to…”
Section: Introduction Backgroundmentioning
confidence: 99%